Assessing Healthcare Providers’ Knowledge of Deferasirox at District Hospitals in Kedah State, Malaysia - Yap, Yae Tyug; Suan, Mohd Azri Mohd; Ismail, Che Kalsom; Chin, Siew Ching; Khor, Chee Hau; Abdullah, Siti Asmak Wan (Journal of Pharmacy Practice and Community Medicine)
Background: Knowledge on Deferasirox among healthcare providers is essential in managing thalassemia patient that require this iron chelator. This study is conducted to assess the knowledge of healthcare providers on Deferasirox at the district hospital in Kedah using a newly developed questionnaire. Methods: The questionnaire consisted of 25 questions was developed via content and face validation, and was assessed for its internal consistency reliability using Cronbach’s alpha coefficient. The newly developed questionnaire was then tested (pilot study) to measure the knowledge level of healthcare providers on Deferasirox in five district hospitals in Kedah state. The association between the level of knowledge and respondents’ characteristics were also measured. Results: Cronbach’s alpha for the new questionnaire was 0.820. A total of 93 respondents participated in the pilot study. The majority of the healthcare providers (54.8%) has a moderate level of knowledge of Deferasirox. Respondents age group (p=0.002), duration of working experience (p=0.005), and type of occupation (p<0.001) were significantly associated with the level of knowledge. Overall, the pharmacist has a better knowledge level. Respondents within the older age group, working experience of less than a year and more than ten years, and staff nurses displayed a low level of knowledge. Conclusion: Future training on the use of Deferasirox should be targeted to the group of staff with the low level of knowledge. Knowledge sharing among the staff can be implemented to reduce the knowledge gap. The pharmacist can play a vital role in the medication counselling regarding Deferasirox with the patients in district hospitals.
Keywords: Deferasirox; Iron chelator; Knowledge; Healthcare provider; Questionnaire